2012
DOI: 10.1016/j.dental.2012.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quaternary ammonium and silver nanoparticle-containing adhesives on dentin bond strength and dental plaque microcosm biofilms

Abstract: Objectives Antibacterial bonding agents are promising to hinder the residual and invading bacteria at the tooth-restoration interfaces. The objectives of this study were to develop an antibacterial bonding agent by incorporation of quaternary ammonium dimethacrylate (QADM) and nanoparticles of silver (NAg), and to investigate the effect of QADM-NAg adhesive and primer on dentin bond strength and plaque microcosm biofilm response for the first time. Methods Scotchbond Multi-Purpose adhesive and primer were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
254
0
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(269 citation statements)
references
References 55 publications
2
254
0
13
Order By: Relevance
“…However, sulfur-containing monomers inhibit the polymerization of resins initiated by the BPO-amine redox systems [20]. Therefore, Super-Bond C & B is the preferred cement for use in combination with sulfur-containing primers, as it uses tri-n-butylborane (TBBO) as the initiator [20]. As for adhesive primers for precious metal alloys: the effectiveness of each primer for each metal is different so it cannot be generalized about which would be better.…”
Section: Second Generation Adhesion Systems [19-21]mentioning
confidence: 99%
See 2 more Smart Citations
“…However, sulfur-containing monomers inhibit the polymerization of resins initiated by the BPO-amine redox systems [20]. Therefore, Super-Bond C & B is the preferred cement for use in combination with sulfur-containing primers, as it uses tri-n-butylborane (TBBO) as the initiator [20]. As for adhesive primers for precious metal alloys: the effectiveness of each primer for each metal is different so it cannot be generalized about which would be better.…”
Section: Second Generation Adhesion Systems [19-21]mentioning
confidence: 99%
“…They all contain sulfur, which seems to react with precious alloys. However, sulfur-containing monomers inhibit the polymerization of resins initiated by the BPO-amine redox systems [20]. Therefore, Super-Bond C & B is the preferred cement for use in combination with sulfur-containing primers, as it uses tri-n-butylborane (TBBO) as the initiator [20].…”
Section: Second Generation Adhesion Systems [19-21]mentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial effect against two E. faecalis strains (ATCC and an endodontic isolate) were assessed, and results had shown that addition of QPEI nanoparticles improved the killing ability of PCS against biofilms of both E. faecalis strains and the effects of AH Plus on the biomass of biofilms from the ATCC strain. Moreover, there were no relevant changes in physicochemical and 95) quaternary ammonium polyethyleneimine QPEI unpolymerizable composite resin 24) , endodontic materials [89][90][91] quaternary ammonium dimethacrylate QADM/IMQ polymerizable composite resin [25][26][27]32) , adhesive system 42) 2-methacryloxylethyl dodecyl methyl ammonium bromide MAE-DB polymerizable composite resin 28,29) 2-methacryloxylethyl hexadecyl methyl ammonium bromide MAE-HB polymerizable composite resin 28,29) 2-Dimethyl-2-dodecyl-1-methacryloxyethyl ammonium iodine DDMAI polymerizable composite resin 30) quaternary ammonium methacrylate QAM polymerizable composite resin 31) , adhesive system 5,53,54) 2-methacryloyloxyethyl phosphorylcholine MPC polymerizable composite resin 33) dimethylaminododecyl methacrylate DMADDM polymerizable adhesive system [43][44][45] quaternary ammonium methacrylate polymer QAMP unpolymerizable adhesive system [46][47][48] methacryloxylethyl cetyl ammonium chloride DMAE-CB polymerizable adhesive system [49][50][51][52] benzalkonium chloride BAC unpolymerizable adhesive system [55][56][57] , glass ionomer cement 73,74) , endodontic materials 87) poly-2-methacry...…”
Section: Endodontic Materialsmentioning
confidence: 99%
“…It had contact inhibitory effect against the bacteria after curing, and prevented bacteria from invading the deep dentin through bonding interface, thus reducing the prevalence of secondary caries and prolonging the service life of the restoration 41) . Accordingly, Zhang et al 42) had studied the effects of QADM and NAg incorporation to an adhesive system, Scotchbond Multi-Purpose (SBMP). It has been shown that adding QADM and NAg in both adhesive and primer had the strongest antimicrobial activity, while reducing metabolic activity, CFU, and lactic acid by an order of magnitude compared with control.…”
Section: Adhesive Systemmentioning
confidence: 99%